Morphological evolution of silica scales in the freshwater genus Synura (Stramenopiles) - Jadrná, Iva; Siver, Peter A; Škaloud, Pavel (Journal of phycology, 2021)
A high degree of morphological variability is expressed between the ornately sculptured siliceous scales formed by species in the chrysophycean genus, Synura. In this study, we aimed to uncover the general principles and trends underlying the evolution of scale morphology in this genus. We assessed the relationships among thirty extant Synura species using a robust molecular analysis that included six genes, coupled with morphological characterization of the species-specific scales. The analysis was further enriched with addition of morphological information from fossil specimens and by including the unique modern species, Synura punctulosa. We inferred the phylogenetic position of the morphologically unique S. punctulosa, to be an ancient Synura lineage related to S. splendida in the section Curtispinae. Some morphological traits, including development of a keel or a labyrinth ribbing pattern on the scale, appeared once in evolution, whereas other structures, such as a hexagonal meshwork pattern, originated independently several times over geologic time. We further uncovered numerous construction principles governing scale morphology and evolution, as follows: (i) scale roundness and pore diameter decreased during evolution; (ii) elongated scales became strengthened by a higher number of struts or ribs; (iii) as a consequence of scale biogenesis, scales with spines possessed smaller basal holes than scales with a keel and; and (iv) the keel area was proportional to scale area, indicating its potential value in strengthening the scale against breakage.
Keywords: molekulární evoluce; Heterokontophyta; oxid křemičitý; Fresh Water; biologická evoluce; zkameněliny; morphology; Biological Evolution; sladká voda; molecular; Fossils; silica scales; microalgae; Silicon Dioxide; fylogeneze; construction principles; chrysophytes; synurophytes; Synura punctulosa; phylogeny; Stramenopiles; ultrastructure; Phylogeny; Evolution, Molecular